Analisis Kebijakan Penolakan Bantuan Negara-negara G7 dalam Mengatasi Kasus Kebakaran Hutan Amazon 2019 - Nasution, Calvin Alhafiz; N, Praja Firdaus (Global and Policy Journal of International Relations, 2022)
President Jair Bolsonaro's policy of refusing foreign aid offered by European countries to deal withthe Amazon forest fire problem in Brazil in 2019 from the analysis level at the individual level. Inthis study also explained about the importance of the Amazon rainforest so it is very interesting bymany countries from around the world to offer assistance in dealing with fires. In receiving aid,Brazilian President Jair Bolsonaro only focused on receiving aid from neighboring South Americancountries and took a stand to believe in the solidarity of Brazil's Latin American neighbors to breakaway from dependence on Europe. In analyzing the problem of forest fires that occurred and whatmade President Jair Bolsonaro choose to reject the assistance offered by the G7 member countries,the authors analyze using a psychobiographical review, idiosyncratic factors, and the character ofthe leader which shows that the policy is related to personal sentiments. President Jair Bolsonaroagainst the offer of assistance made by French President Emmanuel Macron as a representative ofthe G7 member countries.Keywords: Foreign Policy, Individual Analysis, Jail Bolsonaro, Amazon, Foreign AidDOI: https://doi.org/10.33005/jgp.v10i01.3573